Lisbon’s unequal mobilities: the sociospatial differentiation of metropolitan travel behaviors - Caeiro, T.; Carmo, R. M.; Almeida, J.; Mourato, J. (Mid-term Conference: Public Spaces and Private Lives in the Contemporary City - ESA (European Sociological Association, Research Network 37, 2014)
For the last two decades, the Lisbon Metropolitan Area (LMA) expansion model has been highly dependent on car use widening the potential distances of daily mobility (Salgueiro, 2001; Costa, 2007). One of the goals of the research project LOCALWAYS (2013-2015 PTDC/ATP-EUR/5023/2012) is to understand the relation between space mobility and urban sprawl as it impacts on social fragmentation and people’s ability to participate in urban life. This implies connecting mobility to spatial justice issues (Harvey, 1973; Fainstein, 2009; Soja, 2010) as well as debating the right to the city (Lefebvre, 1968; UNHABITAT 2010) or to space in general. People’s mobility is underpinned by urban space production yet its patterns are built through people’s appropriation strategies that reproduce inequality trends beyond space. The resources and ability to move are not equally distributed. Thus, urban mobility is simultaneously an outcome and a driver of exclusion. Taking stock of the results of a LMA-wide survey the presentation will discuss how age, gender, class and space interact in mobility behaviors. Is there a tension between a freer though individualized way to move and live in LMA and a more restrained yet collective participation in urban displacements? In what ways private and public mobility, or even immobility, can reflect privileged conditions or lack of alternatives? Accordingly, we point out fundamental challenges to public policies since social inequality in mobility practices is still quite invisible in policy studies and strategies.